ANALISIS KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA SMP PADA MATERI BANGUN RUANG SISI DATAR - Agustiana, Eka; Imami, Adi Ihsan (IKIP Siliwangi, 2021)
This study aims to determine how the ability of students to think critically in juinor high school students in the discussion of flat-sided shapes. The approach in this research is a qualitative approach and the method used is a descriptive method carried out at one of the MTs schools in Bekasi Regency with a total of 10 students of class IX.3 as the subject. In this study, the data collection technique used was to test the students’ ability to think critically in the form of essay test questions on the discussion of flat-sided shapes.The data analysis technique used the Miles and Huberman analysis technique which consisted of three stages, namely data reduction, data display and conclusion. Based on the research results obtained, the students abality to think critically on the Reason indicator is the highest percentage compared to other indicators, namely 53%, followed by situation indicator, which is 43%, while the Overview indicator is 35% and the Inference indicator is 26%.